A presença de gêneros da esfera da propaganda no livro didático de língua portuguesa - Costa, Sueli da (2009)
This study discusses the treatment given to the publicity and propaganda contents present in elementary school teaching books that are used in Portuguese classes, in public state schools. The presence of what we call propaganda sphere genres (ads, outdoors, flyers, leaflets, among others) in teaching books has been the target of polemics for a long time, above all, from the part of people who are not experts in the teaching-learning of languages. We have considered and discussed the polemics starting from the official documents - Parâmetros Curriculares Nacionais de Língua Portuguesa and Temas Transversais (Portuguese National Syllabus Parameters and Transversal Themes) and from governmental publications and general media, given the judicial dimension the subject has grown into. It is known that those tensions have not prevented the circulation of publicity and propaganda in the teaching material, which we support, not only because of the official documents but also because of the certainty that beyond the verbal-visual and creativity aspects, those genres and the sphere in which they are produced, need to be analyzed and learned in a critical way by students, who are routinely exposed to the product/service idea present in flyers, ads and outdoors, to name a few. It can t be ignored that such sphere, interested supporting (commercial or not), offering and promulgating ideologies along with products and ideas, suggesting/creating behaviors and a series of values linked to consumption, to the symbolic. Supported by discursive - enunciative studies belonging to the Bakthin ideas we approached, initially, the origins and the socio-historic route of the terms publicity and propaganda, emphasizing the works of its sphere of production, circulation and reception. There we observed the existence of interests, not always clear, in taking them as synonyms. Aware all the abone of all mentioned aspects, we selected for analysis two book collections that were part of the 2005 edition of Programa Nacional do Livro Didático (PNLD Didactic Book National Program). Our motivation to choose those collections was the fact that they were approved by the mentioned program, one with restrictions and the other with distinction. The research methodology relied, firstly on a quantitative survey regarding the circulation of publicity and propaganda in the collections (all) evaluated and approved by PNLD/2005, which revealed an expressive presence of genres. In this case, we considered as source the basis of the documents originated from the Projeto Integrado de Pesquisa O livro didático de Língua Portuguesa no ensino fundamental: Produção, Perfil e Circulação (Research Integrated Project The Portuguese teaching book in elementary school: production, features and circulation), CNPq/IELUNICAMP/ CEALE-UFMG, a research projectt analyses the data from PNLD, creating a series of data bases. The obtained data indicated that the genres of the propaganda sphere are expressively contemplated, from a quantitative point of view; regarding the approaches used, it was observed that expressive attention is given to the constituent elements of the genres (compositional form, style and theme), mainly, in activities focused on reading. Though proposals for linguistic analysis and textual production were presented, they were fewer in quantity, in this frequency order. The analysis also showed that one of the collections the one recommended with restrictions prioritized the ads, and also concentrating on the workings of the propaganda sphere